Predictive dual-scale finite element simulation for hole expansion failure of ferrite-bainite steel. (January 2021) - Park, Siwook; Jung, Jinwook; Cho, Woojin; Jeong, Byeong-Seok; Na, Hyuntaek; Kim, Sung-Il; Lee, Myoung-Gyu; Han, Heung Nam
Abstract: A dual-scale finite element model is proposed to investigate the failure of ferrite-bainite (FB) dual-phase steel in the hole expansion test. The first level simulation solves the elastic-plastic deformation behavior with phenomenological isotropic elastic-anisotropic plastic constitutive models, and its resulting local deformation histories are supplied to the second level simulation as boundary conditions. In the second level simulation, the local microstructure evolution is solved and provides the dislocation densities, equivalent plastic strains, and stress triaxiality that measure the local fracture in grain scale. A special formulation for calculating the dislocation density distribution in the form of dislocation pile-up at grain boundary areas is highlighted as the microscale level constitutive law. The microstructural information is provided from image analyses based on grain average image quality (GavgIQ) and grain average misorientation (GAM) values observed using electron backscatter diffraction (EBSD). The data were used to identify the constituent phases of the FB steel as the major input for the microstructure-based representative volume element (RVE). Nanoindentation tests are employed to validate the identified phase and to extract the phase-level mechanical properties. The onset of failure at the hole edge during the hole expansion test is simulated by the proposed dual-scale numerical approach. Thus, both the hole expansion ratio (HER) and the location of failure can be successfully predicted. The example clarifies that the present approach based on local deformation histories and the resultant microstructure evolution with grain-level deformation inhomogeneity can be utilized for understanding the deformation and fracture of multi-phase steels. Graphical abstract: Image 1 Highlights: A dual-scale finite element model is developed to simulate the hole expansion formability of a ferrite-bainite steel sheet. The phase identification is conducted using grain average image quality and grain average misorientation. The RVE model can be a practical tool for analyzing the grain boundary hardening and inhomogeneous plastic deformation. The fracture criterion as a function of stress triaxiality was determined in the context of proposed dual scale simulation.